Targeting epithelial-mesenchymal transition signaling pathways with Dietary Phytocompounds and repurposed drug combinations for overcoming drug resistance in various cancers - A.N.K.V. Sravani; John Thomas (Heliyon)
The epithelial-to-mesenchymal transition (EMT) is a crucial step in metastasis formation. It enhances the ability of cancer cells' to self-renew and initiate tumors, while also increasing resistance to apoptosis and chemotherapy. Among the signaling pathways a few signaling pathways such as Notch, TGF-beta, and Wnt-beta catenin are critically involved in the epithelial-to-mesenchymal transition (EMT) acquisition. Therefore, regulating EMT is a key strategy for controlling malignant cell behavior. This is done by interconnecting other signaling pathways in many cancer types. Although there is extensive preclinical evidence regarding EMT's function in the development of cancer, there is still a deficiency in clinical translation at the therapeutic level. Thus, there is a need for medications that are both highly effective and with low cytotoxic for modulating EMT transitions at ground level. Thus, this led to the study of the evaluation and efficiency of phytochemicals found in dietary sources of fruits and vegetables and also the combination of small molecular repurposed drugs that can enhance the effectiveness of traditional cancer treatments. This review summarises major EMT-associated pathways and their cross talks with their mechanistic insights and the role of different dietary phytochemicals (curcumin, ginger, fennel, black pepper, and clove) and their natural analogs and also repurposed drugs (metformin, statin, chloroquine, and vitamin D) which are commonly used in regulating EMT in various preclinical studies. This review also investigates the concept of low-toxicity and broad spectrum (“The Halifax Project”) approach which can help for site targeting of several key pathways and their mechanism. We also discuss the mechanisms of action, models for our dietary phytochemicals, and repurposed drugs and their combinations used to identify potential anti-EMT activities. Additionally, we also analyzed existing literature and proposed new directions for accelerating the discovery of novel drug candidates that are safe to administer.